Development Of The Village Innovation Ambassador Information System With Scrum Method - Setiawan, Denny; Fatimah, Fety; Primasari, Dewi (Ibn Khaldun International Journal of Applied Sciences and Sustainability, 2023)
Bappedalitbang Bogor Regency while organize an activity Village Innovation Ambassador need to record all college student from various university with their inovation that they created as the result from this activity. There are problems that Bappedalitbang Bogor Regency faced because the amount of college student is plentiful and the data that has been registered is hard to managed as earlier they only use google form for recording the data. The purpose of this research is to solve the problems that Bappedalitbang Bogor Regency have by developing a website-based information system to record the data from Village Innovation Ambassador activitiy which later will be named as Neng Dinda. The system that will be developed by the author will be used by Bappedalitbang Bogor Regency with the requirement as to record the Village Innovation Ambassador data and then display the data as distribution map for the college studen with their inovation and after that the college student will be given an e-sertificate. This data collection system will be developed with PHP framework Laravel and will using development method Agile Development with Scrum model. System development is carried out gradually divided into 4 sprints. The result from each sprint are tested using Black-Box Testing with Equivalence Partition model to make sure every function on the system is working as it should be